Co-breeding Association of Aedes albopictus (Skuse) and Aedes aegypti (Linnaeus) (Diptera: Culicidae) in Relation to Location and Container Size - Nur Aida Hashim; Abu Hassan Ahmad; Anita Talib; Farida Athaillah; Kumara Thevan Krishnan (Tropical Life Sciences Research, 2018)
The occurrence of major outbreaks of dengue, and other vector borne diseases such as chikungunya and zika in tropical and subtropical regions has rendered control of the diseases a top-priority for many affected countries including Malaysia. Control of the mosquito vectors Aedes aegypti and Aedes albopictus through the reduction of breeding sites and the application of insecticides to kill immature forms and adults are the main control efforts to combat these diseases. The present study describes the association between Ae. albopictus and Ae. aegypti in shared breeding sites. This study is important given that any measure taken against one species may affect the other. A yearlong larval survey was conducted in four dengue endemic areas of Penang Island. Sorenson’s coefficient index indicated that no association between number of the immatures of the two species regardless of container size and study location. Therefore, the mean number Ae. Albopictus immature was not decreased in the presence of Ae. aegypti in shared breeding container. However Ae. aegypti appeared to prefer breeding in habitats not occupied by Ae. albopictus, the two species sharing breeding sites only where available containers were limited. In control efforts, eliminating the preferred breeding containers for one species might not affect or reduce the population of the other species. Berlakunya wabak denggi, dan lain-lain penyakit bawaan vektor seperti chikungunya dan Zika di kawasan tropika dan subtropika telah menjadikan kawalan penyakit-penyakit tersebut sebagai keutamaan di negara-negara yang terjejas termasuk Malaysia. Kawalan nyamuk vektor Aedes aegypti dan Aedes albopictus melalui pengurangan tempat pembiakan dan penggunaan racun serangga untuk membunuh jentik-jentik dan nyamuk dewasa adalah usaha utama kawalan bagi memerangi penyakit-penyakit ini. Kajian ini menerangkan tentang hubungan di antara Ae. albopictus dan Ae. aegypti di dalam tempat pembiakan yang dikongsi bersama. Kajian ini penting memandangkan apa jua langkah kawalan yang diambil terhadap satu spesies boleh menjejaskan spesies yang lain. Tinjauan jentik-jentik selama setahun telah dijalankan di empat kawasan endemik denggi di Pulau Pinang. Indeks pekali Sorenson menunjukkan bahawa tiada perkaitan di antara jumlah jentik-jentik bagi kedua-dua spesies tanpa mengira saiz bekas dan lokasi kajian. Oleh itu, min bilangan jentik-jentik Ae. albopictus tidak menurun dengan kehadiran Ae. Aegypti di dalam bekas pembiakan yang sama. Walau bagaimanapun Ae. aegypti lebih gemar membiak di habitat yang tidak diduduki oleh Ae. albopictus, kedua-dua spesies hanya berkongsi tempat pembiakan apabila bilangan bekas yang ada adalah terhad. Dalam usaha kawalan, menghapuskan bekas pembiakan yang digemari oleh satu spesies mungkin tidak memberi kesan atau mengurangkan populasi spesies lain.